1998
DOI: 10.1099/00207713-48-3-635
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis and intrageneric structure of the genus Hyphomicrobium and the related genus Filomicrobium

Abstract: I nst it ut fur Al lg emei ne Mi kro biologie, U n iversitat Kiel, Am Botanischen Garten 1-9, 0-241 18 Kiel, Germany Almost complete 16s rDNA sequences from the type strains of seven species of the genus Hyphomicrobium and of Filomicrobium fusiforme have been determined. The Hyphomicrobium species form two phylogenetic clusters that are only moderately related to each other. While cluster I contains the type species Hyphomicrobium vulgare, Hyphomicrobium aestuarii, Hyphomicrobium hollandicum and Hyphomicrobium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 26 publications
2
35
0
Order By: Relevance
“…Bar, 0.01 nt substitutions per nt position. Clusters I and II were defined by Rainey et al (1998). Other algorithms including maximum-parsimony and maximum-likelihood were also used to compare and determine the topological stability of the phylogenetic trees; these algorithms gave nearly the same topology as shown in this figure.…”
Section: Strain Slg5b-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Bar, 0.01 nt substitutions per nt position. Clusters I and II were defined by Rainey et al (1998). Other algorithms including maximum-parsimony and maximum-likelihood were also used to compare and determine the topological stability of the phylogenetic trees; these algorithms gave nearly the same topology as shown in this figure.…”
Section: Strain Slg5b-19mentioning
confidence: 99%
“…F. fusiforme produced poor growth on solid media. Microcolonies of 0.1-0.2 mm in diameter with a rough surface were observed after 3 weeks incubation at 25 u C. Filomicrobium strains are non-motile and do not use C 1 compounds as carbon sources, characteristics that enable them to be differentiated from members of the genus Hyphomicrobium (Rainey et al, 1998). The genus Hyphomicrobium currently contains 12 recognized species and can be divided into two phylogenetic clusters by the genus Filomicrobium in the phylogenetic tree based on 16S rRNA gene sequence analysis (Rainey et al, 1998; also shown in Fig.…”
mentioning
confidence: 99%
“…In DNA G+C content, members of the newly established family Xanthobacteraceae are highly similar (66-69?1 mol%), whereas the species of the family Hyphomicrobiaceae Babudieri 1950 have high heterogeneity (59-71?4 mol%) (Raj, 1983;Dreyfus et al, 1988;Schlesner et al, 1990;Rainey et al, 1998;Kelly et al, 2000;Fritz et al, 2004). Based on the deep branching observed in 16S rRNA gene sequence-based phylogenetic analysis, we propose a novel family, Xanthobacteraceae fam.…”
Section: The Cluster Of the Order 'Rhizobiales'mentioning
confidence: 99%
“…A 21 bp gap already described for N. nitrogenifigens (Addison et al, 2007) was present in the 16S rRNA gene sequence of strain FSW06-204d T between base positions 1256 and 1278 (E. coli numbering, Brosius et al, 1981). This 21 bp gap was not present in other recognized species of the family Sphingomonadaceae but occurred frequently in other members of the class Alphaproteobacteria, for example, in Filomicrobium fusiforme DSM 5304 T and the closely related Rhodobium marinum DSM 2698 T , but not in other closely related species (Rainey et al, 1998). In contrast, the gap seemed to be a common feature only within the family Rhodobacteraceae, as observed by searching within the ARB database (Ludwig et al, 2004).…”
mentioning
confidence: 99%